ACCURACY AND PRECISION OF AN INDOOR AUTONOMOUS MOBILE ROBOT LOCALIZATION UTILIZING A RFID READER MFRC522 - Harsa Dhani (Universitas Katolik Widya Karya Malang, 2023)
To properly navigate inside a factory or a building, a mobile robot should know its position relative to the working environment. The estimation of the robot position based on sensors interpretation is called localization. One particular method of localization is by the utilization of Radio Frequency Identification (RFID) tags mounted on the floor and a RFID reader and an antenna installed on the robot. When the robot reads a particular tag, the robot can estimate its position. The aim of this research is to examine the accuracy and the precision of mobile robot localization equipped with RFID reader MFRC522 which detects chip less tag MIFARE S50. A mobile robot with four wheels was put on a position and a tag along with a ruler was attached on 60 cm ahead. When the robot detected the tag, it stopped, and the stop positions were recorded for accuracy and precision. The robot gained accuracy of 6,3 cm and precision of between 0,867 cm dan 1,263 cm. The prominent factors affecting inaccuracy and imprecision were the robot speed and the lack of braking mechanism. However, the results are still reasonable for indoor mobile robot application in relative to the robot size.